Combination therapy for the management of mucocele and ranula in children: case series - Rai, Amita; Koirala, Bandana; Dali, Mamta; Shrestha, Sneha (Journal of Chitwan Medical College, 2022)
Mucoceles and ranulas are common cystic lesions affecting the oral mucosa. They typically appear as bluish, often fluctuant, nontender submucosal masses with a normal overlying mucosa. Combination therapy, comprising of micromarsupialization with intralesional steroid administration is a conservative management technique for the management of large mucoceles and ranulas. This case series reports three cases, in which combination therapy was chosen for the management of a large mucocele and ranulas in six, seven and nine-year-old children, respectively. There was complete resolution of all the swellings with no recurrence in any of the cases until the six months follow-up visit. Combination therapy showed promising outcomes as a conservative treatment modality, especially in pediatric population for the management of large mucoceles and ranulas.